Malnutrition in Patients with Atrial Fibrillation: A Systematic Review of Nutritional Scores as Predictors of Arrhythmia Recurrence, Clinical Outcomes, and Long-Term Mortality - Assayed, Amro; Gruhonjic, Hanan; Minasyan, Ashot; Fabian, Daniel; Ramos-Vega, Kiven W.; Ledonio, Charles; Prashad, Rakesh (Cardiology and Cardiovascular Medicine, 2026)
Malnutrition is increasingly recognized as a critical determinant of adverse outcomes in patients with atrial fibrillation (AF), particularly among elderly populations. Despite advances in AF management, the relationship between nutritional status and arrhythmia recurrence, clinical complications, and long-term mortality remains underexplored. This systematic review synthesizes evidence from twenty studies evaluating the prognostic value of validated nutritional assessment tools, including the Controlling Nutritional Status (CONUT) score, Prognostic Nutritional Index (PNI), Geriatric Nutritional Risk Index (GNRI), Mini-Nutritional Assessment—Short Form (MNA-SF), and Global Leadership Initiative on Malnutrition (GLIM) criteria, in patients with AF. Across these studies, malnutrition prevalence ranged from 13% to over 60%, with poor nutritional status consistently associated with higher rates of arrhythmia recurrence following catheter ablation, greater incidence of adverse clinical events such as major bleeding, thromboembolic complications, and hospitalizations, and increased longterm all-cause mortality. Specific nutritional cutoffs, such as CONUT ≥2, PNI <40, GNRI <92, and MNA-SF ≤11, were identified as independent predictors of unfavorable outcomes. Malnourished patients demonstrated a significantly higher risk of post-procedural AF recurrence and mortality even after adjustment for age, comorbidities, and anticoagulation therapy. These findings underscore the importance of routine nutritional screening and early identification of malnourished individuals to optimize risk stratification and inform tailored therapeutic strategies. Integrating nutritional assessment into standard clinical care may improve prognostication and guide interventions aimed at reducing AF-related morbidity and mortality, ultimately enhancing patient outcomes in this high-risk population.